The Influence of Fintech Technology Usage in Islamic Banking on Customer Service and Customer Growth - Resa Yasmine; Ahmad Syakir; Wahyu Syarvina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Indonesia's economic growth is primarily driven by the development of digital technology that has transformed various aspects of life, including banking, transportation, and finance. Fintech, one of the key aspects of this development, includes various banking services such as mobile banking, internet banking, SMS banking, QR Codes, e-money, and ATMs. The purpose of this research is to determine the level of development and understanding of fintech among the public, as well as to assess the public's interest in using fintech products themselves. The research method used in this study is quantitative. The government has emphasized the importance of fintech in the Islamic world, particularly in Indonesia, due to concerns regarding investor trust, lack of knowledge about fintech, and the differences between traditional and Islamic fintech. The government allocates five points for fintech startups, where 81.75 percent of the public understands fintech and uses it without fear.